Conflict in lebanese banks toward lifting banking secrecy. BOD members vs Compliance managers - Ghinda Y. HAMDAR (Proche-Orient Études en management, 2019)
This paper aims to explore potential conflict of interest between BOD membersand compliance managers in Lebanese banks while facing the internationalpressure of transparency that oppresses banking secrecy worldwide.